A Case study of "GMA Network News" as a different type of television news program - Cantos, Maria Socorro C.
This study is aimed at determining the factors that make GMA Network News a different type of television news program. It is the only local news program so far that has deviated from the traditional way of presenting the news. This study was undertaken in the hope of learning more about its deviation. There were two research methods used, namely; content analysis and interviews. There were four aspects of the news program that were analyzed, and these were: 1) the segments included in the program; 2) changes in the news presentation adapted by the program; 3) the newscasters' techniques and mistakes; 4) the program's packaging to attract viewers and sponsors. Results of the content analysis showed that there are more segments now than in the former GMA Network News. The use of Filipino and English languages enable the viewers to easily understand the news stories. The program is fast-paced so that more news stories can be reported. Graphic designs with colorful backgrounds are used as backdrop to distinguish each segment from one another. More video footages and location shots can be seen in the news program to allow the audience a clearer understanding to the news stories. The newscasters are made to stand and smile while delivering the news. They chat with each other before the end of the program. This conveys warmth, sincerity and friendliness to the viewers. The new GMA Network News has been transformed into one resembling a news magazine format. Results of the interviews revealed that the change in audience preference is a big factor by which the producers of GMA Network News have to consider. There is a very large C-D market at night and this C-D crowd is the predominant viewer group of late-night television. The news program adapted to the change in the audience. The producers repackaged the news program by introducing innovations to make it more appealing to this new set of viewers. These findings have both positive and negative implications. While GMA Network News brings a fresh and new approach to news presentation by deviating from the traditional, formal way of presenting news, to a more relaxed and friendly manner and transforming itself into a news magazine format that makes the program more appealing to a large number of audience, the producers should not use this deviation as a marketing strategy mainly for a desire to stay high in the ratings and more revenue for the station, but they have to be true to their program's objectives of informing and serving the public.